Acupressure for Pain of Osteoarthritis : A Systematic Review - Mahanani, Srinalesti; Kertia, Nyoman; Madyaningrum, Ema; Lismidiati, Wiwin (Journal Of Nursing Practice, 2023)
Background: Osteoarthritis can be defined as a disorder of movable joints characterized by deterioration of articular cartilage; osteophyte formation and bone remodeling; changes in periarticular tissues; and a low-grade, nonpurulent inflammation of variable degree. Acupressure is a traditional non-pharmacological intervention that promotes blood circulation and muscle activity. Purpose: This review aimed to investigate the efficacy of acupressure as a complementary therapy method for the pain of osteoarthritis. Methods: Four electronic databases were searched from PubMed, ProQuest, Scopus, and The Cochrane Library use PICO strategy. In studies comparing acupressure with sham acupuncture, no intervention, or conventional intervention was eligible for inclusion. Article study is published on 2012-2022, using English and design RCT and Quasi-experiment. Prisma analysis was used in selection process. The risk of bias in the included studies was assessed using the Joanna Briggs Institute Critical Appraisal Tools for Quasi-Experimental Studies and Randomized Controlled Trials. Results: There were 12 reports selected for review with the homogeny of knee Osteoarthritis. Outcomes were either objectively- or subjectively assessed improvements in specific pain parameters and safety for clinical use. Results showed more clinical trials with proper methodology are needed to confirm the effectiveness of acupressure for the pain of Osteoarthritis. The results of the review showed a positive effect in reducing pain level with acupressure intervention as either the main or complementary therapy. Conclusion: This systematic review shows that acupressure as a single or complementary intervention provides significant benefits in the management of Osteoarthritis. Further trials with a more rigorous design are needed to further validate and address the limitations of the current evidence.